Designing the Clamp System with the Emergency Braking System in the trains by using PLC and SCADA - Ustundag, Aybike; Gencer, Cetin (Ieee, 2021)
As a result of the developments in rail technologies, the vehicles and equipment used in these systems are also developing rapidly. It is in a rapid technological development in vehicles used in rail systems. The resistance forces affecting the movement of the rail system vehicles try to prevent its movement. In addition, the incident adherence and skidding that occur during the course of the rail system vehicles play an important role in the movements of these vehicles. Calculation of forces affecting the movement of rail system vehicles and designing these vehicles accordingly is also important for the safety of these vehicles. When braking is applied on a train running at a certain speed; It stops for a certain time and distance according to road condition, braking and speed on the train. The distance traveled until braking and stopping is the braking distance. Trains have an emergency braking system, but this system locks the train wheels. In this study along with the Anti-Lock Braking System (ABS), the rail clamping system was designed with PLC and SCADA. By using the ABS used in cars on the locomotive and wagons of the train, it is aimed to lock the wheels when the train brakes and to prevent the train from derailment in case of sudden braking with the rail clamp system.
IEEE 11th Annual Computing and Communication Workshop and Conference (CCWC) -- JAN 27-30, 2021 -- ELECTR NETWORK
Keywords: PLC; SCADA; train